The Use of a Game-Based Decision Aid to Educate Pregnant Women about Prenatal Screening: A Randomized Controlled Study - Rothwell, Erin; Johnson, Erin; Wong, Bob; Rose, Nancy C.; Latendresse, Gwen; Altizer, Roger; Zagal, Jose; Smid, Marcela; Watson, Abby; Botkin, Jeffrey R. (American Journal of Perinatology, 2019)
Purpose This project developed and evaluated the efficacy of a game decision aid among pregnant women about prenatal screening in a randomized controlled study.Study Design Participants were recruited from an obstetric clinic of an academic urban medical center and randomized (n = 73) to one of two study groups: the control group (n = 39) that used a brochure or the intervention group (n = 34) that also used a game decision aid.Result Participants who played the game had higher knowledge scores (m = 21.41, standard deviation [SD] = 1.74) than participants in the control group (m = 19.59; SD = 3.31), p = 0.004. The median time of game playing was 6:43 minutes (range: 2:17–16:44). The groups were similar in frequency of completing screening after the study, control = 6 (15%) versus intervention = 11 (32%), p = 0.087. However, the more interaction with the game resulted in more positive attitudes toward screening.Conclusion The addition of a game decision aid was effective in educating pregnant women about prenatal screening. As other genetic testing decisions continue to increase within clinical care, game-based decision tools may be a constructive method of informed decision-making.
Keywords: prenatal screening; decision aid; games; randomized controlled study; education